Study of feasibility and acceptability of screen and treat approach for cervical cancer prevention - Kaur, Kirandeep; Kaur, Amrit Pal; Bagga, Permeet Kaur; Jyothi (International Journal of Research in Medical Sciences, 2024)
Background: Cervical cancer is the fourth most prevalent cancer among women globally, with approximately 604,000 new cases and 342,000 deaths reported Worldwide according to GLOBOCAN 2022. In India, cervical cancer ranks as the second most common cancer cervical cancer accounts for 6-29% of all malignancies in women in India. Most patients with cervical cancer in India are diagnosed at an advanced stage. Cervical cancer is both preventable and curable if detected early through proper screening. Methods: The present study is a prospective study of 1 year which included 500 patients between age 30-50 years, selected after verifying inclusion and exclusion criteria. All the women were screened using VIA and underwent treatment with thermocoagulation. Immediate side effects and side effects at 3 and 6 monthly follow up visits were noted. Results: In this study, a total of 500 women participated. The VIA positivity rate was 11.4%., 94.7% women underwent thermocoagulation. The mean VAS score for pain was 3.815±0.772. During 3 monthly followup visit, 25.92% females reported discharge per vaginum. No side effects were reported at 6 month follow up visit. The case detection rate was 6.4%. The positive predictive value (PPV) was 59.2%. Conclusions: VIA is an excellent alternative to cytology and other expensive screening methods in resource-limited settings like ours. Similarly, thermocoagulation is a quick and straightforward procedure to perform. Utilizing VIA for screening and thermocoagulation as a treatment method has high acceptability among patients, with no significant side effects, making it a safe treatment option.